2015
DOI: 10.1007/s11270-015-2326-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Adsorption Application of In Situ Photo-Cross-Linked Electrospun Poly(Vinyl Alcohol)-Based Nanofiber Membranes

Abstract: Poly(vinyl alcohol)/maleic anhydride/acryloyl thioamide monomer (PVA/MA/ATM) nanofiber membranes (NFm) were synthesized by a combination of UV radiation and an electrospinning technique. The PVA/MA/ATM NFm were characterized by Fourier transform infrared spectroscopy (FT-IR), thermogravimetric analysis (TGA), Brunauer-Emmert-Teller (BET) analysis, scanning electron microscopy (SEM), and energy dispersion spectrometry (EDS). These membranes were used for adsorption-desorption of platinum (Pt(IV)) and palladium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…In addition to chitosan, other positively charged NFs are being investigated as heavy metal adsorbents. Zeytuncu et al prepared PVA/(maleic anhydride)/acryloyl thioamide monomer NF mats using a combination of electrospinning and UV irradiation [40]. The mats revealed a maximum adsorption of 69.…”
Section: Anion-exchange Nanofiber Membranesmentioning
confidence: 99%
“…In addition to chitosan, other positively charged NFs are being investigated as heavy metal adsorbents. Zeytuncu et al prepared PVA/(maleic anhydride)/acryloyl thioamide monomer NF mats using a combination of electrospinning and UV irradiation [40]. The mats revealed a maximum adsorption of 69.…”
Section: Anion-exchange Nanofiber Membranesmentioning
confidence: 99%
“…Zeytuncu et al . prepared poly(vinyl alcohol)/(maleic anhydride)/acryloyl thioamide monomer nanofibrous membranes by a combination of electrospinning and UV irradiation . The maximum adsorption capacities of Pt 4+ and Pd 2+ at 45°C were found to be 69.93 and 112.36 mg g −1 , respectively.…”
Section: Applications Of Ion‐exchange Nanofibersmentioning
confidence: 99%
“…In this study, different approaches were used for crosslinking of PCLF:PCL nanofibers. Recently, in situ photo‐crosslinking has been used for crosslinking of different polymers such as gelatin, poly(vinyl alcohol), methacrylated polycarbonate and hybrids of polyurethane/methacrylated poly(ethylene glycol) during electrospinning . In the mentioned studies, the methacrylate group was activated when exposed to light, and by creating crosslinking bonds (with opening of double carbon bonds) produced from elastomeric properties in fabricated nanofibers.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, in situ photo-crosslinking has been used for crosslinking of different polymers such as gelatin, poly(vinyl alcohol), methacrylated polycarbonate and hybrids of polyurethane/methacrylated poly(ethylene glycol) during electrospinning. [35][36][37][38] In the mentioned studies, the methacrylate group was activated when exposed to light, and by creating crosslinking bonds (with opening of double carbon bonds) produced from elastomeric properties in fabricated nanofibers. Since the mechanism for creating crosslinking bonds by the fumaryl group is similar to methacrylate, in situ photo-crosslinking was examined for crosslinking of PCLF in this research and results (mechanical properties and dissolution test) showed that no crosslinking was occurred in the structure of nanofibers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation